2015
DOI: 10.1155/2015/150649
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Fixation Angle between Polyaxial Pedicle Screw Head and Rod on the Failure of Screw-Rod Connection

Abstract: Introduction. Polyaxial screws had been only tested according to the ASTM standards (when they were perpendicularly positioned to the rod). In this study, effects of the pedicle screws angled fixation to the rod on the mechanical properties of fixation were investigated. Materials and Method. 30 vertically fixed screws and 30 screws fixed with angle were used in the study. Screws were used in three different diameters which were 6.5 mm, 7.0 mm, and 7.5 mm, in equal numbers. Axial pull-out and flexion moment te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Similar results have been obtained in the work of Çetin et al . [44] who found that pullout strength of angled pedicle screws is lower than that of axial pullout strength.…”
Section: Interaction Effect Of Factors On Pullout Strengthmentioning
confidence: 99%
“…Similar results have been obtained in the work of Çetin et al . [44] who found that pullout strength of angled pedicle screws is lower than that of axial pullout strength.…”
Section: Interaction Effect Of Factors On Pullout Strengthmentioning
confidence: 99%
“…Postoperative complications are common, and patients with CSA should be monitored diligently to prevent additional morbidity. 25 Augmented screws (cement) 25 Bicortical fixation 18 Extend construct 25 Stability at the site of Charcot Anterior column reconstruction 25 or shorten anterior column for circumferential stability 19,28 Four-rod construct Increased rod stiffness (eg, cobalt chrome or cobalt chrome plus over titanium alloy or commercially pure titanium) 28,29 Increased rod diameter (6.0 mm diameter over 5.5 or 4.75 mm diameter rods) 28 Fixed angle screws adjacent to the Charcot site 31 Features of construct Construct should incorporate previous fusion 25 Extend to pelvis 26 Consider four-rod construct 25 Correct deformity and restore sagittal balance 26,27 Circumferential fusion Intralesional débridement, AP grafting 26 AP structural grafting 17 Autograft preferred over allograft 19 Augment fusion with BMP 19 BMP = bone morphogenetic protein Description: Methods of obtaining and maintaining surgical principles of stability in the surgical treatment of Charcot spine arthropathy.…”
Section: Discussionmentioning
confidence: 99%
“…The prebent titanium rod was held as perpendicular as possible to the screw rod to ensure that the screw head was parallel to the screw rod. A parallel surface between the screw head and screw rod has been shown to have a higher pull-out stiffness compared with an angled position (15). Preparation of the endplate was then performed carefully, and a cage filled with crushed bone from the removed lamina and facet joint was subsequently inserted into the intervertebral space through the symptomatic side.…”
Section: Surgical Interventionmentioning
confidence: 99%